2004
DOI: 10.1097/01.ju.0000106083.51860.ca
|View full text |Cite
|
Sign up to set email alerts
|

Tape Related Complications of the Tension-Free Vaginal Tape Procedure

Abstract: Urologists should be aware of the nature and symptoms of tape related complications associated with a TVT procedure for prompt diagnosis and appropriate postoperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
2
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 18 publications
0
47
2
13
Order By: Relevance
“…The published incidence rate of urinary retention after single incision sling surgery for incontinence has been reported to be 3.2% [17]. In another study, the incidence rate of urethral obstruction after synthetic sling surgery for incontinence has been reported to be 20% [18]. In our study, however, urinary retention rate was 3.47%, but none of the patients suffered permanent retention.…”
Section: Discussioncontrasting
confidence: 55%
“…The published incidence rate of urinary retention after single incision sling surgery for incontinence has been reported to be 3.2% [17]. In another study, the incidence rate of urethral obstruction after synthetic sling surgery for incontinence has been reported to be 20% [18]. In our study, however, urinary retention rate was 3.47%, but none of the patients suffered permanent retention.…”
Section: Discussioncontrasting
confidence: 55%
“…The presence of mesh within the bladder may arise either from direct bladder perforation, which is missed at cystoscopy (if done) or from subsequent erosion of a submucosal sling [8]. It is often difficult to distinguish retrospectively between these two events.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are two reports of failed endoscopic removal of cut but adherent tape requiring an open procedure [8,28]. Bladder stones are crushed mechanically or with the lithoclast, while tape is either cut flush with the bladder wall and extracted whole, or resected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been rapidly gaining popularity worldwide. Recent studies reported high cure rates of 78.9% to 84.7% after long-term follow-up [15,16] and described relatively low intraoperative and postoperative complication rates [17]. However, there are few published short-term studies on the outcomes of the TVT procedure in overweight and obese women [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%